Vergabe an die Öffentliche Hand Rekommunalisierung im Vergaberecht zwischen Daseinsvorsorge, Wettbewerb und dem Grundsatz der Ausschreibungsfreiheit der Eigenerledigung - Eisentraut, Nikolas (Beiträge zum Vergaberecht (BZV), 2021)
»Awarding to Public Authorities«: Public authorities are increasingly appearing themselves as bidders in procurement procedures in order to remunicipalise services of general interest. Based on EU-primary, constitutional and public procurement law, the thesis examines whether and which procurement obligations public authorities are subject to. In addition, it considers possibilities of a remunicipalisation-friendly design of the award procedure.